MODULATORY ACTIVITY OF BEE POLLEN AGAINST THE TOXICITY OF ANTITUBERCULOSIS DRUGS RIFAMPICIN AND ISONIAZID IN TESTIS OF SPRAGUE DAWLEY RATS - Bharti, Umesh; Kumar, Neelima R; Kaur, Jaspreet (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study is assessment of protective role of bee pollen in antituberculosis drug (rifampicin and isoniazid)-induced toxicity in testis of Sprague Dawley rats. Methods: Healthy rats weighing 180±20 g were selected for the study. Rats were divided into five groups, i.e., Group A (control), Group B (100 mg/kg body weight/day rifampicin-treated), Group C (rifampicin 100 mg/kg body weight and bee pollen 100 mg/kg body weight), Group D (isoniazid 50 mg/kg body/day treated), and Group E (isoniazid 50 mg/kg body weight/day with bee pollen 100 mg/kg body weight/day) serve as experimental groups. Results: Aqueous extract of bee pollen when administered along with the antituberculosis drugs (rifampicin, isoniazid) showed significant reduction in the level of malondialdehyde while the activity of superoxide dismutase, glutathione (GSH) reductase, glutathione peroxidase, glutathioneS-transferase, catalase, and GSH was elevated representing the antioxidant potential of bee pollen against the drug-treated groups. Supplementation of bee pollen significantly reduced histological changes in the testis of drug-induced groups such as smaller epithelial height, germ cell loss, and irregular seminiferous tubules to near normal. Conclusion: Bee pollen has shown the modulatory effect against damage and oxidative stress induced by antituberculosis drugs (rifampicin and isoniazid) in rat testis.